Generalized Clausal Modifiers in Thai Noun Phrases. (December 2014) - Jenks, Peter
Abstract The Thai particle thîi introduces relative clauses and noun‐complement clauses but does not introduce clausal complements of verbs. This paper provides a unified analysis for these two noun phrase‐internal clauses as modifiers, proposing that thîi is a complementizer that is interpreted as a lambda‐operator that derives CP‐sized properties. This analysis is extended to the use of thîi in factive complements of verbs, contrastive clefts, and infinitives. Arguments are presented against the analysis of thîi by den Dikken & Singhapreecha (2004) as a linker, a reflex of DP‐internal predicate inversion.